Validation and Invariance of the Dental Anxiety Scale in a Brazilian sample - Bonafé, Fernanda Salloume Sampaio; Campos, Juliana Alvares Duarte Bonini (FapUNIFESP (SciELO), 2016)
The aim of this study was to evaluate the properties of the Dental Anxiety Scale (DAS) when applied to Brazilian adults and to test its invariance across independent samples and different sociodemographic groups. Sociodemographic data, reports on previous unpleasant dental experiences and DAS responses were collected through telephone interviews. Metric properties of the one and two-factor models were evaluated using confirmatory factor analysis. The analysis included the chi-square ratio divided by degrees of freedom (χ2/df), the comparative fit index (CFI), the goodness of fit index (GFI) and the root mean square error of approximation (RMSEA). Convergent validity was evaluated using the average variance extracted (AVE). Cronbach's alpha (α) and composite reliability (CR) were calculated. In the two-factor model, discriminant validity was evaluated. The invariance of the models was evaluated using a multigroup analysis of the independent samples (pΔχ2λ, pΔχ2 i and pΔχ2 Res ≥ 0.05). Telephone interviews were held with 350 individuals (74.3% women). Of the participants, 135 (38.6%) had previous unpleasant dental experiences, and 117 (33.4%) knew someone who had had this type of experience. The one- and two-factor model (χ2/df < 2.0; CFI,GFI > 0.90; RMSEA < 0.10; AVE > 0.50; α,CR > 0.70) were adjusted to the data. Discriminant validity was limited (ρ2 = 0.66). Both models presented strong invariance across independent samples, but the invariance was weak (pΔχ2i < 0.05) when samples were defined by socioeconomic variables. In conclusion, both DAS models were valid and reliable when applied to a sample of Brazilian adults. However, the weak invariance of the models suggests that sample characteristics interfered with the measurement of dental anxiety.